A Concept for Applying VR and AR Technologies to Support Efficient 3D Non-contact Model Digitalization - Schoor, Wolfram; Masik, Steffen; Tumler, Johannes; Adler, Simon; Hofmann, Marc; Trostmann, Erik (2009 IEEE Virtual Reality Conference, 2009)
In this paper a new interactive digitization concept for large real world objects is described using the virtual reality (VR) environment Elbe Dom. The method combines augmented reality (AR) technologies with a high quality display of textured three dimensional (3D) models. One focus is thereby the display of valuable information of the actual measuring process. The proposed method is a non-contact technique, especially applicable to objects with freeform and a size up to 5 m times 5 m times 3 m. The method achieves an accuracy value of less than 1 mm within the whole measuring volume.